Humanitarian Determinant of Development - RedkoО. Y. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The extended analysis of the phenomenon of parochialism in the Ukrainian context is made. Arguments are given that parochialism has been the dominant behavior mode in Ukraine throughout the independence years. Its negative consequences for the governance performance in Ukraine are shown. In the national science system the parochialism is expressed in extreme conservatism, stagnation of the science system and degradation of the education system. The ways the parochialism affects the national science system are shown, with emphasizing the specific Ukrainian phenomenon of parochialism in the science system: veneration of titles and awards, on the one hand, and active demand for them, on the other. Parochialism has not bypassed the national culture. In the culture context it is demonstrated that the dominance of parochial attitude in Ukraine makes it radically different from the tolerant Europe, which association is sought for by Ukraine. The impact of the parochial mentality on emigration is highlighted: because parochial mentality judges critically the abilities of individuals in their own region or country, because top positions are already occupied and nepotism does not allow a stranger to get through to social lift, career expectations make individuals seek for emigration. Yet, paradoxically, given the system crisis in Ukraine, it is the parochialism that holds together different layers of society and helps preserve the unitary status of the Ukrainian state. Ukraine is likely to live with parochialism for a very long, with the unknown outcome.